Plant diversity scaled by growth forms along spatial and environmental gradients (2004)
Northwester Amazonian forest conservation a challenge for ecologists. The actual deforestation rates in Amazonian rain forests are extremely high. The worst case scenario could lead to an almost total disappearance of largest tropical forest mass that no wades exists on the earth, in a relatively short time (Laurance el al. 2001). Patterns of rain forest plant diversity in this area reaches exceptional high values per unit area (Gentry 1988a, Valencia et al. 1994, ter Steege et al.20039 To guarantee an effective conservation planning, basic knowledge on the distribution of individual species assemblages is necessary. In spite of the fact that information concerning to plan communities has much increased in the last decade; most studies have focused on the trees because they are the most conspicuous elements in the forests (Gentry 1988b, Duivenvoorden 1995, 1996 Pitman et al. 1999 , 2001,ter Steege et al. 2000, Condit ET al.2002). However, it is well known that vascular plant diversity in tropical rain forests in also well represent by other growth forms, such as climebers, shrubs, epiphytes and herb (Gentry and Dobson 1987, Divenvoorden 1994, Balslev et al . 1998, Galeano et al .1998).